(untitled) (Nigerian Dental Journal, 2025)
Objectives: To assess the intra-device repeatability in tooth shade matching with the VITA Easy shade advance V spectrophotometer Materials and Method: This is a cross-sectional clinical study. Twenty six teeth (Incisor-Premolar, being the aesthetic region) that met the selection criteria were included in the study. Spectrophotometric shade matchings of the teeth were done using VITA Easyshade advance V digital dental spectrophotometer. Three consecutive shade readings were taken by the device and recorded for each participant. Data collected was entered into personal computer spread sheet and analysis was done using IBM Statistical Package for Social Science (SPSS) software version 23. The statistical significance was set at <0.05. Results: A total of twenty six (26) participants were recruited for the study. There were 11 (42.3%) males and 15 (57.7%) females. Half (50.0%) of the participants were aged 20-39 years. The first and second consecutive shades selected using the spectrophotometer were the same for 13 (50%) teeth. At the second and third consecutive shade selections, the instrument selected identical shades for 20 (76.9%) teeth. In addition, the same shades were recorded by the spectrophotometer for 17 (65.4%) at the first and third shade selection, while same shade reading were gotten for 12 (46.2%) three consecutive times. There were none of the cases in which all the three shade selected by the spectrophotometer differed. Intra-device reliability for the three consecutive reading measured with Cohen’s Kappa coefficient was 0.39. Conclusions: Instrumental tooth shade matching with VITA Easy shade advance V spectrophotometer enabled repeatable measurement.